Wisdom within: unlocking the potential of big data for nursing regulators. (30th August 2016) - Blumer, L.; Giblin, C.; Lemermeyer, G.; Kwan, J.A.
Abstract : Aim: This paper explores the potential for incorporating big data in nursing regulators' decision‐making and policy development. Big data, commonly described as the extensive volume of information that individuals and agencies generate daily, is a concept familiar to the business community but is only beginning to be explored by the public sector. Background: Using insights gained from a recent research project, the College and Association of Registered Nurses of Alberta, in Canada is creating an organizational culture of data‐driven decision‐making throughout its regulatory and professional functions. The goal is to enable the organization to respond quickly and profoundly to nursing issues in a rapidly changing healthcare environment. Sources of evidence: The evidence includes a review of the Learning from Experience: Improving the Process of Internationally Educated Nurses' Applications for Registration (LFE) research project (2011–2016), combined with a literature review on data‐driven decision‐making within nursing and healthcare settings, and the incorporation of big data in the private and public sectors, primarily in North America. Discussion: This paper discusses experience and, more broadly, how data can enhance the rigour and integrity of nursing and health policy. Conclusion: Nursing regulatory bodies have access to extensive data, and the opportunity to use these data to inform decision‐making and policy development by investing in how it is captured, analysed and incorporated into decision‐making processes. Implications for Nursing and Health Policy: Understanding and using big data is a critical part of developing relevant, sound and credible policy. Rigorous collection and analysis of big data supports the integrity of the evidence used by nurse regulators in developing nursing and health policy.